2012
DOI: 10.1177/2045125312464103
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epigallocatechin gallate supplementation in schizophrenia and bipolar disorder: an 8-week, randomized, double-blind, placebo-controlled study

Abstract: There was no signal for a therapeutic effect of the green tea extract EGCG on psychiatric symptoms in this placebo-controlled pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
1
14
0
2
Order By: Relevance
“…Preclinical studies suggest that the green tea extract with the main polyphenol epigallocatechin-3-gallate (EGCG) may possibly benefit patients with schizophrenia. Loftis et al [ 157 ] were interested in whether EGCG at doses of 600 mg per day is a useful adjunct for maintenance treatment with antipsychotic medication in 34 patients in the double-blind and placebo controlled study. Authors have not found therapeutic effects of EGCG on psychotic symptoms in comparison to placebo.…”
Section: Schizophreniamentioning
confidence: 99%
“…Preclinical studies suggest that the green tea extract with the main polyphenol epigallocatechin-3-gallate (EGCG) may possibly benefit patients with schizophrenia. Loftis et al [ 157 ] were interested in whether EGCG at doses of 600 mg per day is a useful adjunct for maintenance treatment with antipsychotic medication in 34 patients in the double-blind and placebo controlled study. Authors have not found therapeutic effects of EGCG on psychotic symptoms in comparison to placebo.…”
Section: Schizophreniamentioning
confidence: 99%
“…Finally, EGCG is also related to an emotional improvement, especially in terms of anxiety, as the activity of GABA receptors is modulated [28]. This would explain the decrease in anxiety after administration in CNS diseases, such as schizophrenia [29]. Therefore, the aim of this study was to assess the impact of coconut oil and EGCG on the levels of IL-6 and anxiety related to functional disability in MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52 Among the 34 studies, 28 were studies with the primary objective of efficacy assessment and six were studies for safety assessment. The subjects were healthy (10 studies), obese (seven studies), cancer patients (five studies) or other (12 studies).…”
Section: Resultsmentioning
confidence: 99%